Study on the stability of excavation process of permafrost subgrade slope in Alpine region - Zhilong Zhang; Jiyang Zhang; Jiangang Chen; Jing Luo; Bingbing Lei (Scientific Reports)
Abstract The high-altitude mountainous half-excavated and half-filled embankment slopes primarily focus on the long-term stability of slopes, while the safety evaluation methods for the excavation process have received comparatively less attention. In practical engineering applications, the stability assessment of frozen soil slopes is predominantly based on thawing parameters. However, this approach often overlooks the impact of construction activities on water redistribution—particularly concerning the migration and accumulation of water at the frost-thaw interface—resulting in a less accurate evaluation of slope stability.In this study, we employ the strength reduction method, utilizing the strength reduction coefficient as a safety factor for slope stability assessment. A model for evaluating construction stability in slopes has been established. The findings indicate that lower water content correlates with reduced shear strength at the frost-thaw interface; moreover, both cohesion and internal friction angle of soil samples diminish progressively with increasing water content. Under identical temporal conditions, slopes with gentler gradients exhibit relatively shallower thawing depths and demonstrate enhanced stability.When comparing slopes with equivalent ratios and initial water contents, it was observed that maximum thawing depth in frozen soils decreases over time as construction delays occur; thus, later construction leads to diminished impacts on slope stability alongside accelerated freezing rates. Following excavation activities, safety coefficients initially decline before subsequently rising over time; higher safety coefficients correspond to extended safe construction durations for retaining walls.